A multiplex immunoassay method for simultaneous quantification of iron, vitamin A and inflammation status markers. - Eleanor Brindle; Daniel Stevens; Christopher Crudder; Carol E Levin; Dean Garrett; Chris Lyman; David S Boyle (PLoS ONE)
Deficiencies of vitamin A and iron affect a significant portion of the world's population, and efforts to characterize patterns of these deficiencies are hampered by a lack of measurement tools appropriate for large-scale population-based surveys. Vitamin A and iron are not easily measured directly, so reliable proxy markers for deficiency status have been identified and adopted. Measurement of inflammatory markers is necessary to interpret vitamin A and iron status markers, because circulating levels are altered by inflammation. We developed a multiplex immunoassay method for simultaneous measurement of five markers relevant to assessing inflammation, vitamin A and iron status: α-1-acid glycoprotein, C-reactive protein, retinol binding protein 4, ferritin and soluble transferrin receptor. Serum and plasma specimens were used to optimize the assay protocol. To evaluate assay performance, plasma from 72 volunteers was assayed using the multiplex technique and compared to conventional immunoassay methods for each of the five markers. Results of the new and conventional assay methods were highly correlated (Pearson Correlations of 0.606 to 0.991, p<.0001). Inter-assay imprecision for the multiplex panel varied from 1% to 8%, and all samples fell within the limits of quantification for all assays at a single dilution. Absolute values given by the multiplex and conventional assays differed, indicating a need for further work to devise a new standard curve. This multiplexed micronutrient immunoassay technique has excellent potential as a cost effective tool for use in large-scale deficiency assessment efforts.